Vertebrate Adaptive Immunity—Comparative Insights from a Teleost Model - Dickerson, Harry W.; Findly, Robert Craig (Frontiers in Immunology, 2017)
The channel catfish (Ictalurus punctatus) and the ciliated protozoan parasite Ichthyophthirius multifiliis are used to study pathogen-specific protective immunity. In this review we briefly describe this host-parasite system and discuss the comparative insights it provides on the adaptive immune response of vertebrates. We include studies related to cutaneous mucosal immunity, B cell memory responses, and analyses of αβ T cell receptor repertoires. This host-parasite model has played an important role in elucidating host protective responses to parasite invasion and for comparative studies of vertebrate immunity. Recent findings from bioinformatics analyses of TCR β repertoires suggest that channel catfish preferentially expand specific clonotypes that are stably integrated in the genome. This finding could have broad implications related to diversity in lymphocyte receptors of early vertebrates.